Efficient coupling of topological photonic crystal waveguides based on transverse spin matching mechanism - Bojian Shi; Qi Jia; Xiaoxin Li; Yanxia Zhang; Hang Li; Yanyu Gao; Wenya Gao; Xiaoyu Li; Donghua Tang; Tongtong Zhu; Shan Gao; Jing Yang; et al. (Nature Communications)
Abstract Topological photonic structures have great potential to revolutionize on-chip optical integration due to the merit of robust propagation. However, an equally important issue, i.e., the efficient input and output coupling of topological structure with other elements, has not been systematically addressed. Here, we reveal that the coupling of topological photonic structures does not follow the mode matching principle widely used before, but follows the principle of transverse spin matching (TSM). According to this mechanism, efficient coupling between a topological waveguide (TWG) and a strip waveguide (SWG) is designed theoretically and demonstrated experimentally. Theoretical and experimental transmission efficiencies of 96.3% and 94.2% are respectively obtained, which are much larger than those obtained before. The TSM enabled efficient topological structure coupling guarantees a high overall energy efficiency, and paves the way for compact topological photonic chips.